Structural insights into melatonin receptors. (23rd November 2019) - Stauch, Benjamin; Johansson, Linda C.; Cherezov, Vadim
Abstract : The long‐anticipated high‐resolution structures of the human melatonin G protein‐coupled receptors MT1 and MT2, involved in establishing and maintaining circadian rhythm, were obtained in complex with two melatonin analogs and two approved anti‐insomnia and antidepression drugs using X‐ray free‐electron laser serial femtosecond crystallography. The structures shed light on the overall conformation and unusual structural features of melatonin receptors, as well as their ligand binding sites and the melatonergic pharmacophore, thereby providing insights into receptor subtype selectivity. The structures revealed an occluded orthosteric ligand binding site with a membrane‐buried channel for ligand entry in both receptors, and an additional putative ligand entry path in MT2 from the extracellular side. This unexpected ligand entry mode contributes to facilitating the high specificity with which melatonin receptors bind their cognate ligand and exclude structurally similar molecules such as serotonin, the biosynthetic precursor of melatonin. Finally, the MT2 structure allowed accurate mapping of type 2 diabetes‐related single‐nucleotide polymorphisms, where a clustering of residues in helices I and II on the protein–membrane interface was observed which could potentially influence receptor oligomerization. The role of receptor oligomerization is further discussed in light of the differential interaction of MT1 and MT2 with GPR50, a regulatory melatonin coreceptor. The melatonin receptor structures will facilitate design of selective tool compounds to further dissect the specific physiological function of each receptor subtype as well as provide a structural basis for next‐generation sleeping aids and other drugs targeting these receptors with higher specificity and fewer side effects. Abstract : The two melatonin G protein‐coupled receptors, MT1 and MT2, are involved in the implementation and maintenance of circadian rhythms and are implicated in sleeping disorders, depression, cancer, and diabetes. Recent crystallographic studies provided the structural basis of ligand recognition and subtype selectivity at these receptors and revealed an occluded binding site with a highly unusual ligand access mode via a narrow membrane‐buried channel.